Estradiol and testosterone associated with risk of breast cancer: a meta-analysis: Meta-analysis: Hormones' Role in Breast Cancer Risk - Liu, Yanqing; Kang, Yujuan; Li, Xiaofei; Qu, Nina (Journal of Medical Biochemistry, 2024)
Background: To investigate the correlation between estradiol and testosterone in patients with breast cancer.Methods: The literatures on the correlation between estradiol and testosterone on the risk of breast cancer were searched and collected. The time limit is that each database is established until December 2023. After screening, the modified Jadad scale was used to evaluate the quality of the research literature. NoteExpress 3.2 was used for literature management, and Excel 2003 was used for data collection and extraction. Statistical analysis was performed using RevMan 5.4.1 software to determine whether there was heterogeneity in the study according to the size of Q test (P-value), and then the OR value of combined effects was calculated using fixed or random effects models and forest maps were drawn. At the same time, the literatures with the greatest weight were excluded for sensitivity analysis, and the literature bias was evaluated by drawing funnel plot.Results: A total of 628 literatures were retrieved, and 11 case-control trials met the criteria for inclusion. Meta-analysis results showed that the level of E2 in breast cancer patients was higher than that in non-breast cancer control group, but the difference was not statistically significant (OR=121.56, 95%CI (-3.32-264.44), P=0.06). The level of E2 in premenopausal patients with breast cancer was higher than that in non-breast cancer control group, but the difference was not statistically significant (OR=8.26, 95%CI (-2.83-19.34), P=0.14). The level of E2 in postmenopausal patients with breast cancer was higher than that in non-breast cancer control group, and the difference was statistically significant (OR=20.36, 95%CI (7.04-33.68), P=0.003). Preoperative T level was higher in patients with breast cancer than in non-breast cancer control group, but the difference was not statistically significant (OR=14.77, 95%CI (-14.11-43.65), P=0.32). The T level before and after surgery in breast cancer patients was higher than that in non-breast cancer control group, and the difference was statistically significant (OR=12.91, 95%CI (4.43-21.39), P=0.003). Sensitivity analysis showed that the combined effect size results were stable and reliable OR (95%CI) was 24.41 (10.21~38.61), P=0.0007. Funnel plot results showed publication bias. Conclusion There is a positive correlation between the levels of estradiol and testosterone and the occurrence and development of breast cancer after menopause.
Keywords: estradiol; Testosterone; Breast cancer; meta-analysis